AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI PENILAIAN KINERJA DI DEALER HONDA PLAZA TUBAN KANTOR CABANG BOJONEGORO - Hasan Bisri (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2017)
Accounting information in the form of future information is useful for budget preparation. While accounting information in the form of information in the past is useful as a performance appraisal of central managers accountability and motivation manager. Accounting accountability is very necessary and useful for large companies whose business activities require the division of tasks and responsibilities. This research is a case study on accountancy accounting at Honda Plaza Tuban Dealer Branch Office of Bojonegoro, where the research finds that the Honda Plaza Tuban Branch of Bojonegoro Branch has applied accountancy accountability in assessing the performance of each management level, as well as the implementation of accounting accountability in performance appraisal of each level management at Honda Tuban Dealer Plaza Tuban Branch Bojonegoro has been running effectively.